2016
DOI: 10.1021/acs.energyfuels.6b01074
|View full text |Cite
|
Sign up to set email alerts
|

Initial Deposition Feature during High-Temperature Pressurized Pyrolysis of a Typical Zhundong Coal

Abstract: This work clarifies the diffusion and initial deposition behavior of volatilizable elements during pressurized pyrolysis of a typical Zhundong high-basic (i.e., high proportion of alkali and alkaline earth metallic species, AAEMs) coal. The concentrations of AAEMs in raw coal and its derived char as a function of pyrolysis temperature and pressure were duly measured; besides, the features of innermost deposit in specific areas of pyrolysis reactor were particularly investigated. The release of AAEMs was strong… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 37 publications
(11 citation statements)
references
References 51 publications
0
11
0
Order By: Relevance
“…The other minor chemical forms of Ca, water-soluble and insoluble forms, present negligible variation with O 2 content. The release and transformation of AAEMs are largely related to their occurrence modes with coal . As illustrated in Figure d, the Fe of the insoluble form first increases apparently with the increasing O 2 content in oxy-fuel combustion, and then becomes asymptotically constant, whereas the Fe of the HCl-soluble form shows an opposite evolution compared with the insoluble Fe.…”
Section: Resultsmentioning
confidence: 95%
See 2 more Smart Citations
“…The other minor chemical forms of Ca, water-soluble and insoluble forms, present negligible variation with O 2 content. The release and transformation of AAEMs are largely related to their occurrence modes with coal . As illustrated in Figure d, the Fe of the insoluble form first increases apparently with the increasing O 2 content in oxy-fuel combustion, and then becomes asymptotically constant, whereas the Fe of the HCl-soluble form shows an opposite evolution compared with the insoluble Fe.…”
Section: Resultsmentioning
confidence: 95%
“…Only a small quantity of water-soluble calcium is released or transformed into other chemical forms as the combustion temperature is beyond 1000 °C. However, Lin et al 54 found out that the release of Ca was substantially enhanced with the pyrolysis temperature up to 1000 °C and then kept constant hereafter, while magnesium (Mg) presented a different varying tendency. The transformation behaviors of AAEMs were strongly influenced by the corresponding occurrence modes and thermal conversion conditions.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…For potassium, insoluble potassium is the most abundant form, and the total content of potassium is relatively lower than the total content of sodium. Nevertheless, the results for calcium and magnesium are different from those of previous research . This difference occurred because NH 4 Cl was used as an alternative buffer solution instead of NH 4 OAc solution to determine the contents of ion‐exchangeable Ca and Mg species in the two coals.…”
Section: Resultsmentioning
confidence: 99%
“…It is obvious that alkali and alkaline earth metals are removed by acid-washing. There are four types of alkali and alkaline earth metals found in coal: water-soluble, ion-exchangeable, hydrochloric soluble and stable forms (Lin et al 2016;Bai et al 2017). Among these four types,hydrochloric-soluble alkali metals and alkaline earth metals is organic salt presenting as coordination form in coal structure.…”
Section: Removal Of Inherent Alkali and Alkaline Earth Metals And Itsmentioning
confidence: 99%